Discovery on Goldbach conjecture - Bado, Idriss, Olivier (My University, 2019)
Goldbach's famous conjecture has always fascinated eminent mathematicians. In this paper we give a rigorous proof based on a new formulation, namely, that every even integer has a primo-raduis. Our proof is mainly based on the application of Chebotarev-Artin's theorem, Mertens' formula and the Principle exclusion-inclusion of Moivre.
Keywords: Goldbach conjecture; Chebotarev-Artin theorem; Mertens formula; Moivre